Digital Financial Literacy and Life Satisfaction: Evidence from South Korea - Youngjoo Choung; Tae-Young Pak; Swarn Chatterjee (Behavioral Sciences)
Digital financial literacy is an emerging concept that refers to the ability to effectively use digital tools, platforms, and services to manage personal finances. While previous studies have explored the behavioral effects of digital financial literacy, less is known about its broader well-being implications for financial consumers. In this study, we aim to examine the association between digital financial literacy and life satisfaction in a developed country context. Digital financial literacy was measured using a multidimensional scale that encompasses financial knowledge, digital literacy, digital financial service awareness, practical know-how of digital financial services, and self-protection against digital financial fraud. Using data of 1615 Korean adults who currently use digital financial services, this study estimated a series of regressions linking life satisfaction to digital financial literacy and covariates. The results showed a significant association between digital financial literacy and life satisfaction, with self-protection against fraud being the most influential subdimension. Notably, financial knowledge was not associated with life satisfaction when other dimensions of digital financial literacy were independently included in the regression models. These findings highlight the importance of digital skills and knowledge in navigating digital financial services. They also emphasize the need for targeted policies, financial education initiatives, and consumer protection measures to address the lack of digital financial literacy among marginalized populations.